Working with families in the face of porter drugs with a rights approach - Flórez-Ibarra, Jannet Maribel (2021)
Children, adolescents and young people at the family level are exposed to a variety of risk factors such as street drugs. One of them, smoking, must be reconciled from a legal approach to mitigate this situation within the family. The purpose of this paper is to describe the family influence on smoking and its consequences from the epidemiological, legal and social point of view. Family history of smoking has a significant influence on tobacco consumption.